Desempenho de plantas de canola originadas de sementes microbiolizadas com bactérias promotoras de crescimento - Perboni, Anelise Tessari (2014)
The work aimed to evaluate the photosynthetic traits, growth and production of canola plants originated from seeds microbiolized with growth-promoting bacteria. Sequential tests were developed using different isolates of growth-promoting bacteria in association with canola hybrids. In the first test, 96 isolates were used for the mass selection of growth-promoting bacteria. JIP test parameters obtained from the chlorophyll fluorescence, leaf area and shoot dry weight of the Hyola 433 hybrid were evaluated at 55 days after sowing (DAS). The second test was conducted in two stages with isolates selected in the test I: in the stage I, chlorophyll fluorescence, gas exchange and shoot dry weight of Hyola 433 hybrid were evaluated through three measurements in different periods of the crop cycle; in the stage II, the seedlings emerged, chlorophyll fluorescence, leaf area, leaves, petioles and stems dry weight in plants of the Hyola 61 hybrid were evaluated at 41 DAS. In the third test, the isolated DFs 104, DFs 320, DFs 513 and DFs 628 were used, selected in previous experiments; the seedling emergence, performance indexes, leaf area, dry matter partitioning and chlorophyll index were evaluated during the plants growth. At the end of the experiment, the yield components per plant and grain composition of fatty acids were determined. The correlation between the JIP test parameters and growth variables allowed the determination of interest parameters (F0/FM, FV/F0, ABS/RC, TR0/RC, φPo, PIabs and PItotal) for selection of isolates with potential to promote plant growth. Generally, the JIP test parameters were able to detect changes in the operation of the electron transport chain in plants of different treatments; however the responses were highly variable in each test. Some isolates caused an increase of the growth parameters especially DFs 320, DFs 513 and DFs 628 which also showed trends of increase of yield components. In addition, these isolates did not change the fatty acid composition of canola grains, i.e., the seed microbiolization can promote plant growth without causing changes in the quality of oil obtained. We conclude that chlorophyll fluorescence can be used in the evaluation of photosynthetic responses of plants from seeds microbiolized with bacterial isolates. The seeds microbiolization with bacterial isolates DFs 320 [unidentified], DFs 513 [Pseudomonas veronii] and DFs 628 [Bacillus sp.] promotes increase of Hyola 61 hybrid canola plants growth.